Toxicities and early outcomes in a phase 1 trial of photodynamic therapy for premalignant and early stage head and neck tumors. (April 2016) - Ahn, Peter H.; Quon, Harry; O'Malley, Bert W.; Weinstein, Gregory; Chalian, Ara; Malloy, Kelly; Atkins, Joshua H.; Sollecito, Thomas; Greenberg, Martin; McNulty, Sally; Lin, Alexander; Zhu, Timothy C.; et al.
Highlights: Treating severe dysplasia, carcinoma in situ, and early head and neck cancers is challenging. Treatment with photodynamic therapy with Levulan allows for relatively short-term light precautions. Maximum Tolerable Dose has not been reached in our phase 1 study. It is too early to suggest a dose response for light doses in our study. We find high marginal recurrence rates, suggesting use of generous light fields. Summary: Objectives: Management of early superficial lesions in the head and neck remains complex. We performed a phase 1 trial for high-grade premalignant and early superficial lesions of the head and neck using photodynamic therapy (PDT) with Levulan (ALA). Materials and methods: Thirty-five subjects with high grade dysplasia, carcinoma in situ, or microinvasive (⩽1.5 mm depth) squamous cell carcinoma were enrolled. Cohorts of 3–6 patients were given escalating intraoperative light doses of 50–200 J/cm 2 4–6 h after oral administration of 60 mg/kg ALA. Light at 629–635 nm was delivered in a continuous (unfractionated) or fractionated (two-part) schema. Results: PDT was delivered to 30/35 subjects, with 29 evaluable. There was one death possibly due to the treatment. The regimen was otherwise tolerable, with a 52% rate of grade 3 mucositis which healed within several weeks. Other toxicities were generally grade 1 or 2, including odynophagia (one grade 4), voice alteration (one grade 3), and photosensitivity reactions. One patient developed grade 5 sepsis. With a median follow-up of 42 months, 10 patients (34%) developed local recurrence; 4 of these received 50 J/cm 2 and two each received 100, 150, and 200 J/cm 2 . Ten (34%) patients developed recurrence adjacent to the treated field. There was a 69% complete response rate at 3 months. Conclusions: ALA-PDT is well tolerated. Maximum Tolerated Dose appears to be higher than the highest dose used in this study. Longer followup is required to analyze effect of light dose on local recurrence. High marginal recurrence rates suggest use of larger treatment fields.